2(6x-6)+3=2(2x+3)+5

Simple and best practice solution for 2(6x-6)+3=2(2x+3)+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6x-6)+3=2(2x+3)+5 equation:


Simplifying
2(6x + -6) + 3 = 2(2x + 3) + 5

Reorder the terms:
2(-6 + 6x) + 3 = 2(2x + 3) + 5
(-6 * 2 + 6x * 2) + 3 = 2(2x + 3) + 5
(-12 + 12x) + 3 = 2(2x + 3) + 5

Reorder the terms:
-12 + 3 + 12x = 2(2x + 3) + 5

Combine like terms: -12 + 3 = -9
-9 + 12x = 2(2x + 3) + 5

Reorder the terms:
-9 + 12x = 2(3 + 2x) + 5
-9 + 12x = (3 * 2 + 2x * 2) + 5
-9 + 12x = (6 + 4x) + 5

Reorder the terms:
-9 + 12x = 6 + 5 + 4x

Combine like terms: 6 + 5 = 11
-9 + 12x = 11 + 4x

Solving
-9 + 12x = 11 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-9 + 12x + -4x = 11 + 4x + -4x

Combine like terms: 12x + -4x = 8x
-9 + 8x = 11 + 4x + -4x

Combine like terms: 4x + -4x = 0
-9 + 8x = 11 + 0
-9 + 8x = 11

Add '9' to each side of the equation.
-9 + 9 + 8x = 11 + 9

Combine like terms: -9 + 9 = 0
0 + 8x = 11 + 9
8x = 11 + 9

Combine like terms: 11 + 9 = 20
8x = 20

Divide each side by '8'.
x = 2.5

Simplifying
x = 2.5

See similar equations:

| 8x-4=10x+19 | | 9xz^2-30xz-96x= | | -2x-7(c+3)=-93 | | 1(a-4)=2(2a+4) | | 8x-4=10+19 | | 4-3yi=4x+16i | | -329=-7(7+5p) | | x=0.5+y | | 3(4x-7)=6-(2-5x) | | 8(-8k-1)=5k-8 | | -11=9-2b | | 31=25-x-x | | 4(2x-7)+4=8 | | 3x+4y-z=4 | | 4x+9=10x+3 | | -59=-4n-3 | | 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x | | 10y+5x=30 | | 2c+10=c-2 | | -12x=-228 | | 12x+32=10+y | | 2y^2-6x+1=0 | | 3m^3+192= | | -70=14n | | 12(600)=x | | 2(-3x+5)-6x=-3(x+4) | | 14-5x+9x=-2(-7x+3) | | 8n-17=0 | | x^2-2xy+8=0 | | x-9=3x+15 |

Equations solver categories